Antioxidant and Cytotoxic Effects of Aqueous Extract of Iranian Green Tea (Camellia sinensis L.): Antioxidant and Cytotoxicity of Camellia sinensis - Mitra Mehrabani; Bagher Amirheidari; Negar Ahmadinia; Masoud Forooghi-Nematollahi; Salehe Sabouri (Iranian Journal of Pharmaceutical Sciences, 2022)
Green tea, a common beverage, has several pharmacological effects. In this study, the amounts of phenolic compounds and epigallocatechin (EGC) were determined in an aqueous extract of green tea planted in Lahijan (a city in the north of Iran) by Folin-Ciocalteu method and HPLC, respectively. Antioxidant activity of the extract was measured by DPPH and the FRAP assays. Furthermore, its cytotoxic effect was investigated on HT-29 (colorectal cancer) and 3T3 (normal fibroblast) cell lines, after 24 and 48 h treatment by MTT method. Trypan blue dye exclusion measurement was also done on the HT-29 cells treated with the extract. The results have shown that each gram of the dried extract contains 283.6 ± 10.57 mg total phenolic content and 88.44 ± 1.85 mg EGC. The antioxidant activity of the extract measured by DPPH showed an EC50 value of 84.31 ± 4.14 μg/ml. In the FRAP test, the equivalent amount of Iron (Fe) was 4.45 mmol per g of the dried extract. The extract showed toxicity on the HT-29 cell line with an IC50 value of 82.45 ± 18.39 μg/ml after 48 h treatment. The data were confirmed by trypan blue dye exclusion test. Based on the results, adding green tea to the diet may have many health benefits.